Caricature et censure du dessin politique en France: ou le rôle de la liberté d'expression au sein des médias français de la révolution à l'affaire des caricatures de Mahomet - Henry, Nicolas Christian, author; Malpezzi Price, Paola, advisor; Grim, Frédérique, committee member; Margolf, Diane, committee member (Colorado State University. Libraries, 2012)
The goal of this thesis is to analyze the various changes that led France to become a true democracy by allowing its citizens to express themselves freely. Through social, political, and judicial battles, France successfully gained the right to self-expression without fearing the consequences of potential censorship. However, the war for freedom was never completely acquired. I will emphasize the most notorious cases in which the press was silenced by the censors. I will especially insist on the most modern example with defied French justice. I will provide a historical analysis to understand what led to a unique trial that ignited so much controversy. I will conclude that the legislative and democratic solution reflects the very principles of an independent and egalitarian society.
Text in French; title and abstract in English and French.